2017
DOI: 10.3390/ma10030225
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration of Intended Pozzolanic Reaction under Initial Thermal Treatment for Developing Cementless Fly Ash Based Mortar

Abstract: Without using strong alkaline solution or ordinary Portland cement, a new structural binder consisting of fly ash and hydrated lime was hardened through an intensified pozzolanic reaction. The main experimental variables are the addition of silica fume and initial thermal treatment (60 °C for 3 days). A series of experiments consisting of mechanical testing (compressive and flexural strength, modulus of elasticity), X-ray diffraction, and measurements of the heat of hydration, pore structure, and shrinkage wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 43 publications
1
19
0
Order By: Relevance
“…On the other hand, in the case of SF_15, the first peak of pore diameters moved from 9 to 17 nm between 28 and 91 days (Figure 5c). This movement means that the pores around 10 nm expanded in size (by approximately double), possibly due to the accelerated drying shrinkage with a fine pore structure by excessive SF addition [15,49]. Similarly, Rao has reported that the addition of SF has a significant influence on the drying shrinkage of cement mortar due to the strong pozzolanic reaction and pore size refinement mechanism, especially with 15% (by wt % of cement) SF addition.…”
Section: Investigation On Strength Reductionmentioning
confidence: 93%
See 3 more Smart Citations
“…On the other hand, in the case of SF_15, the first peak of pore diameters moved from 9 to 17 nm between 28 and 91 days (Figure 5c). This movement means that the pores around 10 nm expanded in size (by approximately double), possibly due to the accelerated drying shrinkage with a fine pore structure by excessive SF addition [15,49]. Similarly, Rao has reported that the addition of SF has a significant influence on the drying shrinkage of cement mortar due to the strong pozzolanic reaction and pore size refinement mechanism, especially with 15% (by wt % of cement) SF addition.…”
Section: Investigation On Strength Reductionmentioning
confidence: 93%
“…The measured pore volume was divided into four size ranges in Figure 7, on the basis of the international union of pure and applied chemistry system [45]. However, the micropore range was modified from <1.25 nm to <4.5 nm based on the previous studies which have shown that the enhanced pozzolanic reaction considerably changes the pore structure especially below 4.5 nm range [15,47]. Thus, this modification can help to effectively explain the change of pore structure by the intensified pozzolanic reaction.…”
Section: Porosity Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to this, HPC or UHPC features to include silica fume in their mix proportions (see Table 1). This ultra-fine particle not only acts as a physical filler that fills sub-micro sized voids of concrete, but also contributes to making the concrete stronger by the pozzolanic reaction with water and portlandite which is formed by primary cement hydration [15,16]. The pozzolanic reaction progresses slowly over time, but it is accelerated with increasing curing temperature and eventually contributes to an additional increase in strength.…”
Section: Behavior Of Concrete With Various Strengths and MIX Proportimentioning
confidence: 99%